2021
DOI: 10.1016/j.pacs.2021.100298
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic-guided endovenous laser ablation: Characterization and in vivo canine study

Abstract: Endovenous laser ablation (EVLA) is a minimally invasive surgical procedure, often guided by ultrasound (US) imaging, for treating venous insufficiencies. US imaging limitations in accurately visualizing the catheter and the lack of a temperature monitoring system can lead to sub-optimal outcomes. An integrated photoacoustic (PA)-guided EVLA system has been previously developed and reported to overcome the shortcomings of US-guided procedure. In this study, we further characterized the system and tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…19,152,217 5.4 Photoacoustic-Guided Surgical Navigation PA-guided intervention is a growing research field that is described in several reviews. [218][219][220] Preclinical studies have demonstrated the feasibility of various applications, such as pedicle screw evaluation, 221 catheter-based interventions, 222,223 and liver surgery. 224 In cardiac, catheter-based interventions accurate navigation is essential for diagnosis and effective treatment.…”
Section: Intravascular Photoacoustic Imaging To Identify Vulnerable P...mentioning
confidence: 99%
See 1 more Smart Citation
“…19,152,217 5.4 Photoacoustic-Guided Surgical Navigation PA-guided intervention is a growing research field that is described in several reviews. [218][219][220] Preclinical studies have demonstrated the feasibility of various applications, such as pedicle screw evaluation, 221 catheter-based interventions, 222,223 and liver surgery. 224 In cardiac, catheter-based interventions accurate navigation is essential for diagnosis and effective treatment.…”
Section: Intravascular Photoacoustic Imaging To Identify Vulnerable P...mentioning
confidence: 99%
“…PA-guided intervention is a growing research field that is described in several reviews. 218 220 Preclinical studies have demonstrated the feasibility of various applications, such as pedicle screw evaluation, 221 catheter-based interventions, 222 , 223 and liver surgery. 224 …”
Section: Clinical and Translational Researchmentioning
confidence: 99%
“…The output of PA thermometer was used as the feed-back controller for photothermal therapy [27] . An integrated photoacoustic guided system was developed for endovenous laser ablation [28] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the concept of PA thermometry was developed rstly by Rinat et al in 2005 [20]. Subsequently, PA thermometry has become a valuable feedback modality in the different thermal treatment processes, especially in laser radiation [21][22][23][24]. However, PA signals of the tissue itself are very weak for the low absorption coe cient and are easily affected by noise.…”
Section: Introductionmentioning
confidence: 99%